Penerapan Media Cerita Bergambar Untuk Meningkatkan Kemampuan Membaca Pemahaman Pada Pelajaran Bahasa Indonesia - Adinda Dwi Damayanti; Ibnu Muthi (Lembag, 2024)
This research aims to improve reading comprehension skills using picture story media in class III students. This research is Classroom Action Research (PTK) which is designed to help teachers find and solve problems during the classroom learning process. This classroom action research was carried out in two cycles, with research subjects consisting of 33 class III students. Data collection techniques are observation and tests. The data analysis technique uses quantitative data analysis. The results of research using picture story media for two cycles, the average value of the test results has increased. In cycle I, the first meeting achieved a score of 57% and in the second meeting 63% with the category not yet reaching the KKM and in cycle II there was an increase. The score at the first meeting was 69% and at the second meeting it increased by 100%. This shows that improving reading comprehension skills using picture story media in Indonesian language subjects can be applied further to improve student learning achievement.